Adapting towards digital revolution: strategies for tourism educators in Malaysia - Abdul Karim, Noor Ibtisam; Mohd Puad, Mohd Hazwan; Syed Abdullah, Sharifah Intan Sharina (Human Resources Management Academic Research Society (HRMARS), 2024)
The swift incorporation of digital technologies in the tourist industry has brought about a new paradigm in all facets of higher education offering tourism programs. The COVID-19 pandemic, a global crisis of unprecedented scale, has profoundly impacted tourist education, including learning spaces, teaching methodologies, graduates' job prospects, and curriculum development. These concerns impact tourism educators, who play a crucial role in transmitting information and skills during the teaching and learning process to prepare high-quality and competent graduates. This paper aims to identify the strategies for tourism educators in Malaysia to adapt to the impacts of the digital revolution in tourism education. The analyses have been driven into four adaptation strategies: enhancing the educators’ understanding of the changing nature of tourism work, transforming the tourism educators’ profile, managing tourism educators’ technological knowledge and competencies, and upgrading digital infrastructure and faculty facilities. These recommendations are crucial as they provide a foundation for the respected parties to develop decisive strategies that align with the tourism educators’ needs, abilities, and interests, thereby ensuring a successful adaptation to the digital revolution.